Imaging biomarkers of breast cancers originating from the major lactiferous ducts: Ductal adenocarcinoma of the breast, DAB. Issue 154 (September 2022) - Tabár, László; Dean, Peter B.; Lee Tucker, F.; Chen, Tony Hsiu-Hsi; Smith, Robert A.; Duffy, Stephen W.; Chiu, Sherry Yueh-Hsia; Ku, May Mei-Sheng; Fan, Chiao-Yun; Yen, Amy Ming-Fang
Highlights: Breast cancer of ductal origin (DAB) has six characteristic, easily recognizable imaging biomarkers. DAB can be radiologically distinguished from breast cancers having other sites of origin. The mammographic appearance of DAB shows good concordance with disease outcome. DAB is an invasive malignancy and should not be termed "DCIS". DAB has an insidious natural history and a poor outcome. Management of DAB requires a re-evaluation of this misunderstood breast cancer subtype. Abstract: Purpose: As we have previously demonstrated, breast cancers originating in the major lactiferous ducts and propagating through the process of neoductgenesis are a distinct subtype of invasive breast cancers, although by current practice they are placed within the group termed ductal carcinoma in situ (DCIS) and are consequently underdiagnosed and undertreated. Imaging biomarkers provide a reliable indication of the site of origin of this breast cancer subtype (Ductal Adenocarcinoma of the breast, DAB) and have excellent concordance with long-term patient outcome. In the present paper, the imaging biomarkers of DAB are described in detail to encourage and facilitate its recognition as a distinct, invasive breast cancer subtype. Methods: Correlation of breast imaging biomarkers with the corresponding histopathological findings using large format technology, with additional evidence from subgross, thick section histopathology to demonstrate the complex three-dimensional structure of the newly formed duct-like structures, neoducts. Results: There are six imaging biomarkers (mammographic tumour features) of DAB. Four subgroups have characteristic malignant-type calcifications on the mammogram. Two of these are characterized by intraluminal necrosis producing fragmented or dotted casting type calcifications on the mammogram; another two subgroups are characterized by intraductal fluid production which may eventually calcify, producing skipping stone-like or string of pearl-like calcifications. A fifth DAB subgroup presents with bloody or serous nipple discharge and is usually occult on mammography but is detectable with galactography and magnetic resonance imaging (MRI). The sixth subgroup presents as architectural distortion on the mammogram without associated calcifications. Conclusions: Radiologists can use these well-defined imaging biomarkers to readily detect Ductal Adenocarcinoma of the Breast, DAB. Immunochemical biomarkers are generally not determined from the DAB itself, due to the erroneous assumption that DAB is non-invasive. MRI plays a crucial role in determining disease extent and guiding surgical management. The accumulating evidence that this disease subtype is, in fact, an invasive cancer, necessitates an urgent re-evaluation of the diagnostic and management criteria for this poorly understood malignancy.